(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the ethnolinguistic and psycholinguistic characteristics of the population’s behavior were studied on the basis of sociological surveys and relevant conclusions were drawn. The sociological surveys was carried out using IT technologies through the docs.google platform.